Partisipasi Perajin Dalam Pengembangan Seni Kerajinan Anyaman di Kampung Purun Berbasis Kearifan Lokal - Rusmaniah, Rusmaniah; Nugroho, Dedy Ari; Indriyani, Putri Dyah; Putra, Muhammad Adhitya Hidayat (Universitas Nusantara PGRI Kediri, 2022)
Business actors in the creative economy sector focus on creativity, one of which is the purun woven craft business, while humans have various mindsets and cultures as a result of their habits. This is a challenge in Purun Village to continue to have an existence in the creative economy sector competition so that it requires the participation of craftsmen in the development of woven crafts in Purun Village. This research was conducted to provide an overview of the participation of artisans in the development of woven crafts in Purun Village based on local wisdom. This study used a qualitative approach. Data was collected through in-depth interviews, observation and documentation. Data analysis went through several stages, namely the reduction stage, presentation and conclusion drawing and verification. The results showed that the participation of artisans in the development of woven crafts in Purun Village was based on local wisdom. Among them are: 1) preserving woven from generation to generation 2) making plaits based on local wisdom 3) creating product innovations in accordance with market developments 4) product diversification. In the development of the purun woven craft industry, the role of the crafter is very important, including preserving the purun woven craft by passing it on to the next generation, protecting the environment by utilizing purun which is known as a wild plant, and improving the regional economy.